RENEWABLE ENERGY CONSUMPTION TOWARDS ENVIRONMENTAL SUSTAINABILITY: EVIDENCE OF EKC HYPOTHESIS IN THE FRAMEWORK OF ECONOMIC GROWTH AND CO2 EMISSIONS - Syed Muhammad Faraz Raza; Ikram Ali; Muhammad Yasir Malik; Maaz Ahmad; Syed Zain Ul Abidin; Sadia Masood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This study explores the influence of economic growth and its squared term on carbon dioxide emissions to confirm the EKC U and inverted U shape in developing countries. The study also explores which form of energy benefits environmental sustainability and deterioration. In this research, five countries are selected from South Asia, covering 1995 to 2018. The results of FMOLS and DOLS have proved the EKC inverted U-shaped hypothesis in the long run. Renewable energy consumption and squared economic growth significantly reduce carbon dioxide emissions in the long run. In contrast, fossil fuel energy consumption and economic growth positively enhanced carbon dioxide emissions in the long run. Gross capital formation negatively influences carbon dioxide emissions, while labor productivity contributes to environmental deterioration. The study suggested that South Asian developing countries should adopt renewable energy resources to sustain their environment and overcome greenhouse gases’ environmental hazards. The availability of low-cost renewables should be possible to reduce the demand for fossil fuels at the domestic level will lead to environmental sustainability.